A Review of the Most Common and Economically Important Diseases That Undermine the Cultivation of Tomato Crop in the Mediterranean Basin - Panno, Stefano; Davino, Salvatore; Caruso, Andrea Giovanni; Bertacca, Sofia; Crnogorac, Ana; Mandić, Ana; Noris, Emanuela; Matić, Slavica (Agronomy (Basel), 2021)
Tomato (Solanum lycopersicum L.), family Solanaceae, has become in the past fifty years one of the most important and extensively grown horticultural crops in the Mediterranean region and throughout the world. In 2019, more than 180 million tonnes of tomato have been produced worldwide, out of which around 42 million tonnes in Mediterranean countries. Due to its genetic properties, tomato is afflicted by numerous plant diseases induced by fungal, bacterial, phytoplasma, virus, and viroid pathogens. Not only is its genetic inheritance of great importance to the management of the numerous tomato pathogens, but equally as important are also the present climate changes, the recently revised phytopathological control measures, and the globalization of the seed industry. Thus, the recognition of symptoms and the knowledge of the distribution and spread of the disease and of the methods for early detection of the pathogens are the major prerequisites for a successful management of the disease. In this review, we will describe the main tomato pathogens in the Mediterranean area that impact mostly the tomato yield and provide the current and perspective measures necessary for their successful management.